2020
DOI: 10.3847/2041-8213/abca31
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Radio Observations of Two Repeating Fast Radio Burst Sources: FRB 121102 and FRB 180916.J0158+65

Abstract: The spectra of fast radio bursts (FRBs) encode valuable information about the source's local environment, underlying emission mechanism(s), and the intervening media along the line of sight. We present results from a long-term multiwavelength radio monitoring campaign of two repeating FRB sources, FRB121102 and FRB180916.J0158 +65, with the NASA Deep Space Network(DSN) 70 m radio telescopes (DSS-63 and DSS-14). The observations of FRB121102 were performed simultaneously at 2.3 and 8.4 GHz, and spanned a to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 91 publications
0
25
1
Order By: Relevance
“…None of these bursts have counterparts in the 110-188 MHz band of LOFAR. Similarly, Pearlman et al (2020) used simultaneous CHIME/FRB and DSN 70 m dish observations to demonstrate a burst detection in the CHIME/FRB band but none at 2.3 or 8.4 GHz. Clearly, FRB 20180916B bursts have a low instantaneous bandwidth, as has been seen for FRB 20121102A (Gourdji et al 2019;Majid et al 2020) and beautifully demonstrated for FRB 20190711A (Kumar et al 2021).…”
Section: Spectrotemporal and Polarimetric Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…None of these bursts have counterparts in the 110-188 MHz band of LOFAR. Similarly, Pearlman et al (2020) used simultaneous CHIME/FRB and DSN 70 m dish observations to demonstrate a burst detection in the CHIME/FRB band but none at 2.3 or 8.4 GHz. Clearly, FRB 20180916B bursts have a low instantaneous bandwidth, as has been seen for FRB 20121102A (Gourdji et al 2019;Majid et al 2020) and beautifully demonstrated for FRB 20190711A (Kumar et al 2021).…”
Section: Spectrotemporal and Polarimetric Behaviormentioning
confidence: 99%
“…The detection of low-frequency bursts with no simultaneous high-frequency emission (Pearlman et al 2020) strongly challenges models in which the 16.3 day observed periodicity is the result of absorption by the companion wind . Rather, our LOFAR HBA detections and the lack of any observed DM variations, with ΔDM  0.1 pc cm −3 throughout the active window (PR3), suggest that we have a relatively clean line of sight to the burst source itself.…”
Section: A Self-consistent Model For Frb 20180916bmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-frequency follow-up studies are critical for characterizing FRB sources and emission models. One such approach is to carry out simultaneous observations of FRBs across wide bandwidths (Scholz et al 2017;Majid et al 2020;Pearlman et al 2020;Scholz et al 2020) that are more robust against temporal evolution of scintillation and scattering, as well as arXiv:2105.10987v1 [astro-ph.HE] 23 May 2021 intrinsic short term variability in the emission spectrum of individual bursts. Another approach is to probe the shorter timescales of the bursts to place limits on the instantaneous size of the emitting regions, similar to the studies of the Crab giant pulses carried out with few nanosecond time resolution (Hankins et al 2003).…”
Section: Introductionmentioning
confidence: 99%